Glycated albumin as medium-term glycemic control in diabetes mellitus - Rosyid, Fahrun Nur; Hario Seno, Khristophorus Heri Nugroho; Rahman, Ahmad Fadhlur (International Journal of Research in Medical Sciences, 2021)
Monitoring of glucose levels is essential in preventing the complications of diabetes mellitus, including short, medium and long-term monitoring. Short-term monitoring includes random plasma glucose, fasting plasma glucose, 2-hour post prandial plasma glucose and Oral glucose tolerance tests (OGTT). The medium-term monitoring includes fructosamine and Glycated albumin (GA) while the long-term monitoring is glycated hemoglobin (HbA1c). Currently, the most recommended examination for glucose level monitoring in patients with diabetes mellitus is the glycated hemoglobin (HbA1c). However, there seem to be some conditions where the HbA1c value is doubtful or unreliable. Some of these conditions include anemia, thalassemia, dialysis and pregnancy. The best choice at this time is GA.